Enjeux textuels d’une lecture féministe de la science-fiction - Richard Saint‑Gelais (ReS Futurae, 2023)
Can literary theory, and specifically theories of science fiction, teach us something about feminist readings of science fiction? This paper upholds such a view, while qualifying it at once by adding that the role of theory is not to settle debates by providing authoritative interpretations but to shed light on the stakes of texts as well as of reading strategies. A look on controversies surrounding U. Le Guin’s The Left Hand of Darkness, J. Wyndham’s “Consider Her Ways”, T. Godwin’s “The Cold Equations” and A. Robida’s The Twentieth Century allows us to put forward an array of questions about the role of reading in the shaping of fictional worlds, the identification of the stance tacitly assumed by narratives, and the evaluation of the respective incidence of ideology and formal devices.